2014
DOI: 10.1176/appi.neuropsych.12110332
|View full text |Cite
|
Sign up to set email alerts
|

Skin Conductance Levels May Reflect Emotional Blunting in Behavioral Variant Frontotemporal Dementia

Abstract: Emotional blunting is a core diagnostic feature of behavioral variant frontotemporal dementia (bvFTD). The authors evaluated skin conductance as a measure of emotional blunting among 10 patients with bvFTD compared with 10 with Alzheimer's disease and 14 healthy control subjects. Despite responses to an auditory startle stimulus, skin conductance levels (SCLs) were lower in the patients with bvFTD compared with the other groups. The low SCLs significantly correlated with ratings of emotional blunting. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 28 publications
3
50
2
Order By: Relevance
“…One study linked blunted phasic embarrassment-related, predominantly sympathetic autonomic responses to atrophy of the right pregenual ACC (68). Interestingly, baseline skin conductance level, a measure of sympathetic tone, was recently found to be reduced in patients with bvFTD (72), in contrast to the lack of a significant difference in our study (Table 1). Our experimental setting could have been insensitive to sympathetic deficits due to the calming influence of the scanner environment on healthy control subjects or an activating influence of the scanner on patients.…”
Section: Relationship Of Present Findings To Previous Work On Autonomiccontrasting
confidence: 59%
See 1 more Smart Citation
“…One study linked blunted phasic embarrassment-related, predominantly sympathetic autonomic responses to atrophy of the right pregenual ACC (68). Interestingly, baseline skin conductance level, a measure of sympathetic tone, was recently found to be reduced in patients with bvFTD (72), in contrast to the lack of a significant difference in our study (Table 1). Our experimental setting could have been insensitive to sympathetic deficits due to the calming influence of the scanner environment on healthy control subjects or an activating influence of the scanner on patients.…”
Section: Relationship Of Present Findings To Previous Work On Autonomiccontrasting
confidence: 59%
“…A recent study performed clinical autonomic function tests and reported a high prevalence of parasympathetic and sympathetic dysfunction in bvFTD without exploring the anatomical correlates of these deficits (13). In the context of emotion processing, several studies examined physiological reactivity to emotional stimuli and found that patients with bvFTD retained physiological responses to many stimuli (27,71,72) but that response amplitudes were diminished to emotional stimuli, such as those designed to elicit self-conscious emotions (71). One study linked blunted phasic embarrassment-related, predominantly sympathetic autonomic responses to atrophy of the right pregenual ACC (68).…”
Section: Relationship Of Present Findings To Previous Work On Autonomicmentioning
confidence: 99%
“…To date, few studies have employed psychophysiological techniques to objectively measure emotion processing in FTD, with mixed results. Some studies have reported attenuated skin conductance levels in response to aversive stimuli (loud noise) in bvFTD compared with Alzheimer's disease patients and healthy controls (Hoefer et al, 2008;Joshi et al, 2014). However, others have found no difference in physiological responses to complex emotional film stimuli between healthy controls and a mixed group of bvFTD and SD patients, despite impaired explicit emotion recognition performance in these syndromes (Werner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…9 If autonomic mechanisms contribute to aberrant emotion processing in FTD, one would anticipate associated changes in physiological reactivity, as has previously been documented in FTD syndromes. In particular, bvFTD has been associated with abnormal autonomic reactivity to affectively charged stimuli, [18][19][20][21][22] alterations of resting skin conductance and heart rate variability, 23,24 and abnormal brain-heart coupling, 24,25 while nfvPPA has been associated with reduced pupil responses to arousing stimuli. 20,26 Taken together, these findings are consistent with the known targeting of core cerebral autonomic fronto-cingulo-insular circuitry in bvFTD and nfvPPA.…”
Section: Introductionmentioning
confidence: 99%